The Role of Consumption Emotions in the Satisfaction Response - Phillips, Diane M.; Baumgartner, Hans (Journal of Consumer Psychology, 2002)
We report 2 studies that served to clarify the role of consumption emotions in the satisfaction response. In the 1st study, we examined the role of consumption emotions within the expectancy‐disconfirmation model of consumer satisfaction and investigated whether consumption emotions are a result of product performance or disconfirmation. The findings show that both positive and negative emotions are primarily a function of product performance and influence satisfaction even when the effects of expectations, performance, and disconfirmation are controlled. In the 2nd study, we proposed and tested an alternative framework for understanding the role of consumption emotions in the satisfaction response for situations in which consumers use more of an experiential perspective to anticipate and experience consumption. According to this model, consumers form affective expectations about how consumption of the product will make them feel, experience positive or negative emotions as a result of these expectations and product consumption, and evaluate the discrepancy between experienced and anticipated emotions. All 3 variables, then, impact satisfaction. The results empirically support many of the relations in the new model of the experiential satisfaction response but also raise several interesting avenues for future research.